'A matter of political expediency': Iran, Britain, South Africa and the settlement of Reza Shah's estate. Issue 6 (2nd November 2017) - Bakhash, Shaul
ABSTRACT: When Reza Shah, the former ruler of Iran, died in exile in Johannesburg, South Africa, in 1944, he left some £110, 000 in cash in his bank account and valuables and other items worth another £20, 000. But he left no will; and the Union government proceeded to impose a tax amounting to over £43, 000 (one-third of the total value) and to distribute the remainder among heirs as specified in Union law for persons who had died intestate. Reza Shah's son, Mohammad Reza Shah, the ruling Iranian monarch, hard up for money, fought these requirements. He claimed everything in his late father's possession was his, and that neither estate taxes nor distribution to heirs applied. A four-year battle over the estate ensued. It was eventually resolved, but only after vigorous efforts by two British ambassadors to Tehran, endeavours at the highest levels of the British government; the involvement of the South African prime minister and, finally, an act of the South African parliament. This article examines the intricate tug-of-war surrounding the settlement of the estate of Reza Shah and what it tells us about the principal parties involved.